Culicidae (Diptera: Culicomorpha) in the southern Brazilian collection "Ana Leuch Lozovei" with notes on distribution and diversity (SciELO Preprints, 2022)
Biological collections are of extreme importance in acquiring knowledge of the biodiversity of a specific environment. In this article, we organise, list and catalogue the adult specimens belonging to the family Culicidae housed in the Parasitology Collection of the Basic Pathology Department at the Federal University of Paraná, southern Brazil. To this end, a data bank was created, containing information on the taxonomy and collecting of each sample. The culicids were collected using different methodologies in 18 municipalities in the state of Paraná, between 1967 and 1999. There are 5,739 catalogued specimens of which 4,704 (81.96%) are identified at a specific level, with a diversity of 205 species. Of these, 18 are new recorded samples for the state of Paraná and 3 for Brazil. This being the case, we propose, in honour of the 30 years dedicated to the study of culicids in the state of Paraná, the creation of the Ana Leuch Lozovei Entomological Collection, which is composed of insect vectors or potential vectors, of agents that cause diseases in humans.